2020
DOI: 10.1007/s00376-019-8251-6
|View full text |Cite|
|
Sign up to set email alerts
|

Stratospheric Ozone-induced Cloud Radiative Effects on Antarctic Sea Ice

Abstract: Recent studies demonstrate that the Antarctic Ozone Hole has important influences on Antarctic sea ice. While most of these works have focused on effects associated with atmospheric and oceanic dynamic processes caused by stratospheric ozone changes, here we show that stratospheric ozone-induced cloud radiative effects also play important roles in causing changes in Antarctic sea ice. Our simulations demonstrate that the recovery of the Antarctic Ozone Hole causes decreases in clouds over Southern Hemisphere (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…It results in an increase in vertical temperature gradient which is the largest at the tropopause region and consequent decreases of static stability in the upper troposphere. The changes in static stability further lead to an increase of high clouds at around 300 hPa especially in April and May (Figures 2d–2f), which is consistent with the results in the previous studies (Li & Thompson, 2013; Nowack et al., 2015; Xia et al., 2016, 2018; Xia, Hu, et al., 2020). The correlation analysis further demonstrates that ozone significantly impacts the Arctic high clouds (Figure ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It results in an increase in vertical temperature gradient which is the largest at the tropopause region and consequent decreases of static stability in the upper troposphere. The changes in static stability further lead to an increase of high clouds at around 300 hPa especially in April and May (Figures 2d–2f), which is consistent with the results in the previous studies (Li & Thompson, 2013; Nowack et al., 2015; Xia et al., 2016, 2018; Xia, Hu, et al., 2020). The correlation analysis further demonstrates that ozone significantly impacts the Arctic high clouds (Figure ).…”
Section: Resultssupporting
confidence: 91%
“…(2018) found that the changes in upper tropospheric and lower stratospheric ozone significantly influence the static stability in the upper troposphere and consequent variations of high clouds, which further impact the longwave radiation at surface. Stratospheric ozone‐induced cloud radiative effects result in significant change in Antarctic sea ice, which are comparable to that due to atmospheric and oceanic dynamic processes (Xia, Hu, et al., 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, ozone depletion has been linked to a reduction in downwelling long-wave 19 radiation. This reduction would also cool the Southern Ocean [ 142 , 143 ]. In contrast to these studies, results from state-of-the-art earth-system models clearly indicate that ozone depletion in the second half of the twentieth century should have caused a reduction in sea ice extent, mainly by promoting the redistribution of ocean heat content [ 140 , 141 , 143 145 ].…”
Section: Effects Of Recent Changes In Stratospheric Ozone On Climate ...mentioning
confidence: 99%
“…We calculate the TOA radiative feedbacks using the radiative kernel method introduced by Huang, et al 54 , which has been widely used in decomposition of radiative effects for climate change analysis [55][56][57][58][59][60][61] .…”
Section: Radiative Kernel Decompositionmentioning
confidence: 99%